Monitoring spatiotemporal biogenesis of macromolecular assemblies by pulse-chase epitope labeling - Stelter, Philipp; Kunze, Ruth; Gaik, Monika; Thomson, Emma; Thierbach, Karsten; Thoms, Matthias; Hurt, Ed (Molecular cell, 2012)
Summary: Many cellular proteins perform their roles within macromolecular assemblies. Hence, an understanding of how these multiprotein complexes form is a fundamental question in cell biology. We developed a translation-controlled pulse-chase system that allows time-resolved isolation of newly forming multiprotein complexes in chemical quantities suitable for biochemical and cell biological analysis. The “pulse” is triggered by an unnatural amino acid, which induces immediate translation of an amber stop codon repressed mRNA encoding the protein of interest with a built-in tag for detection and purification. The “chase” is elicited by stopping translation of this bait via a riboswitch in the respective mRNA. Over the course of validating our method, we discovered a distinct time-resolved assembly step during NPC biogenesis and could directly monitor the spatiotemporal maturation of preribosomes via immunofluorescence detection and purification of a pulse-labeled ribosomal protein. Thus, we provide an innovative strategy to study dynamic protein assembly within cellular networks.